Teresa of Jesus, an evangelizer on the web - Pérez González, María José (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
We present the figure of Teresa of Jesús (interconnected woman) from the point of view of her digital media coverage in the occasion of her Vth Centenary (1515-2015). After mentioning some of the websites that have Teresa as the protagonist, we focus on the blog «Teresa, de la rueca a la pluma», edited from the Carmel of Puzol (Valencia). We outline the criteria that guide its edition and some of its features. Finally, we select from the blog two examples that show how Teresa of Jesus keeps on evangelizing today’s world with today’s means.